Diagnosis Using CCTA and Management of Anomalous Right Coronary Artery from the Opposite Sinus - Asma Mursleen; Gregory Hartlage; Aarti Patel; Eric E. Harrison; C. Alberto Morales (Case Reports in Cardiology)
Coronary anomalies can be observed in 1–1.2% of all angiograms performed. Majority of coronary anomalies are benign and do not lead to cardiac ischemia; however anomalous coronary arteries from the opposite sinus (ACAOS) are often associated with sudden cardiac deaths, typically in 0.11–0.35% of individuals who participate in vigorous physical activity (Peñalver et al., 2012). Left and right ACAOS have an incidence of 0.15% and 0.92%, respectively. Left ACAOS are often associated with higher incidence of sudden cardiac death; this could be secondary to greater territory of myocardial perfusion by the left coronary artery. ACAOS are often asymptomatic and initially present as sudden death following exertion in young athletes. The management of left ACAOS is clear and surgery is usually indicated. However there is a lack of consensus on the management of certain cases of right ACAOS. In this paper a case of 20 yo M with right coronary artery from left sinus is going to be presented with a discussion on pathophysiology, diagnosis, and management.